Improving the Environmental Performance of Palm Biodiesel via AgNO₃-Assisted Removal of Polyunsaturated Fatty Acids - Helwani, Zuchra; Zahrina, Ida; Amraini, Said Zul; Idroes, Rinaldi; Neonufa, Godlief Frederick; Rahman, Sunarti Abd (Leuser Journal of Environmental Studies, 2025)
Indonesian biodiesel products commonly exhibit low oxidative stability and high cloud points, which limit their performance and widespread use. These drawbacks are primarily due to the high content of polyunsaturated fatty acids (PUFAs) in the fatty acid methyl ester (FAME) mixture that constitutes biodiesel. A more suitable biodiesel composition includes higher proportions of saturated and monounsaturated fatty acids, which offer better combustion properties, higher cetane numbers, and greater resistance to oxidative degradation. In contrast, PUFAs promote oxidation reactions, resulting in fuel instability, increased sludge formation, and higher emissions of unburned hydrocarbons, negatively impacting both engine performance and the environment.This study investigates the use of silver nitrate (AgNO₃) as a selective extraction agent to remove PUFAs from palm oil-derived FAME. The goal is to identify the most effective biodiesel-to-AgNO₃ volume ratio for separating saturated fatty acid fractions from unsaturated ones, in order to produce a more stable and environmentally friendly biodiesel. Experimental results show that a 1:2 volume ratio significantly reduces the iodine number, from 57.22 to 47.38 g I₂/100 g sample, indicating a decrease in unsaturated compounds. Furthermore, oxidative stability improved from 11.18 hours to 11.69 hours after extraction. The removal of PUFAs not only improves the fuel's storage and combustion stability but also enhances its environmental profile. More stable biodiesel burns more completely, reducing emissions of particulate matter and greenhouse gases, and contributing to cleaner air and lower environmental impact. Thus, PUFA extraction using AgNO₃ presents a promising approach for improving the sustainability and performance of palm-based biodiesel fuels.